Knowledge Oriented Leadership and Knowledge Worker-Performance: The Mediating Role of Knowledge Management Practices, Organizational Commitment and Job Satisfaction - Sulaeman, Moh. Muklis; Haryono, Tulus; Sunaryo, Sinto; Hendarsjah, Hidajat (Journal of Ecohumanism, 2025)
This study aims to analyze the effect of Knowledge-Oriented Leadership on Knowledge Worker Performance by considering the mediating role of Organizational Commitment, Job Satisfaction, and Knowledge Management Practices. This study was conducted at the East Java Nahdlatul Ulama Higher Education Institution (LPTNU), which faces challenges in improving lecturer performance. This study used quantitative methods with a sample of 283 respondents who were permanent lecturers at LPTNU. Data were collected through questionnaires and analyzed using SmartPLS. The results showed that Knowledge-Oriented Leadership has no direct effect on Knowledge Worker Performance. However, this variable has a positive and significant influence on Organizational Commitment and Knowledge Management Practices. In addition, Knowledge Management Practices and Organizational Commitment significantly improve Knowledge Worker Performance. Job Satisfaction was also found to act as a mediator in the relationship between Knowledge-Oriented Leadership and Knowledge Worker Performance. This research contributes to the development of the Knowledge-Based View (KBV) theory by reinforcing the importance of the mediating roles of Organizational Commitment, Job Satisfaction, and Knowledge Management Practices. From a practical perspective, these results provide insights for LPTNU management to strengthen policies that support Knowledge-Oriented Leadership, as well as improve Organizational Commitment and Knowledge Management Practices.